A study on the conduction path in undoped polycrystalline diamond films - Lee, BJ; Ahn, BT; Lee, JK; Baik, YJ (ELSEVIER SCIENCE SA, 2001)
The conduction path in as-grown undoped diamond films deposited by chemical vapor deposition has been investigated by employing impedance spectroscopy, electroplating and electroetching. The thickness- and direction-dependencies of electrical resistivity did not agree with the previously known surface conduction model. The Cu electroplating and Ag electroetching results showed that the current path followed the grain boundaries within the diamond films. The Cu electroplating of diamond film with an insulating surface layer also showed that the grain boundaries within the films were the main conduction path in undoped polycrystalline films. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: HYDROGEN; TRANSPORT